2017
DOI: 10.5194/acp-17-1571-2017
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of nitric acid, ammonia, and organics in orographic clouds: mass spectrometric analyses of droplet residual and interstitial aerosol particles

Abstract: Abstract. Concurrent in situ analyses of interstitial aerosol and cloud droplet residues have been conducted at the Schmücke mountain site during the Hill Cap Cloud Thuringia campaign in central Germany in September and October 2010. Cloud droplets were sampled from warm clouds (temperatures between −3 and +16 • C) by a counterflow virtual impactor and the submicron-sized residues were analyzed by a compact time-of-flight aerosol mass spectrometer (C-ToF-AMS), while the interstitial aerosol composition was mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 91 publications
(148 reference statements)
1
43
1
1
Order By: Relevance
“…S8) possibly reflect the uptake of gaseous HNO 3 during cloud processes (Hayden et al, 2008;Roth et al, 2016). A recent study also confirmed that the update of gaseous HNO 3 is an important contributor for the increased nitrate level in the cloud residuals (Schneider et al, 2017). Interestingly, we observed a decrease in nitrate intensity in all cloud residues except for dust type (Fig.…”
Section: Comparison Of Cloud Residues With Ambient and Nonactivated Psupporting
confidence: 83%
See 2 more Smart Citations
“…S8) possibly reflect the uptake of gaseous HNO 3 during cloud processes (Hayden et al, 2008;Roth et al, 2016). A recent study also confirmed that the update of gaseous HNO 3 is an important contributor for the increased nitrate level in the cloud residuals (Schneider et al, 2017). Interestingly, we observed a decrease in nitrate intensity in all cloud residues except for dust type (Fig.…”
Section: Comparison Of Cloud Residues With Ambient and Nonactivated Psupporting
confidence: 83%
“…These studies were mainly conducted at sites in North America including Wyoming (Pratt et al, 2010a), Ohio (Hayden et al, 2008), Oklahoma (Berg et al, 2009), Florida Twohy et al, 2005) and California (Coggon et al, 2014); in Europe including Schmücke (Roth et al, 2016;Schneider et al, 2017), Jungfraujoch (Kamphus et al, 2010), Åresku-tan (Drewnick et al, 2007) and Scandinavia (Targino et al, 2006); in the Arctic (Zelenyuk et al, 2010); in Central America (Cziczo et al, 2013); in western Africa (Matsuki et al, 2010); and in marine areas (Twohy and Anderson, 2008;Twohy et al, 2009;Shingler et al, 2012).…”
Section: Q Lin Et Al: a Ground-based Counterflow Virtual Impactor Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that qualitative measurements and quantification of organic nitrates are of major interest (e.g., Fry et al, 2009;Bruns et al, 2010;Farmer et al, 2010;Ayres et al, 2015;Kiendler-Scharr et al, 2016;Liu et al, 2017;Schneider et al, 2017). Organic nitrates are decomposed during the evaporation and/or ionisation processes in the C-ToF-AMS and, therefore,…”
Section: Particulate Organic Nitratesmentioning
confidence: 99%
“…Many studies reported on the difficulties to measure organic 10 nitrates quantitatively, but suggested also a possibility to estimate the amount or at least the presence of organic nitrates based on the measured ion ratios of NO + to NO + 2 using aerosol mass spectrometry (e.g., Bruns et al, 2010;Farmer et al, 2010;Rollins et al, 2010;Fry et al, 2013;Ayres et al, 2015;Kiendler-Scharr et al, 2016;Ng et al, 2017;Schneider et al, 2017).…”
mentioning
confidence: 99%